The Efektivitas Metode Bermain (Menggunting dan Menempel) Terhadap Perkembangan Motorik Halus Anak Kelompom A TK Aisyiyah Bustanul Athfal II Tumampua, Pangkep. - Khairunisa Adnan, Khadijah; Andira, Ayu (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Abstract This research was motivated by the child's cutting and sticking ability which still needed to be improved at the Aisyiyah Bustanul Athfal II Kindergarten Tuamampua, Pangkep so that the researchers gave the stages of cutting and pasting in the process of improving children's fine motor skills. The purpose of this study was to determine: 1) learning planning with cutting and sticking activities to improve fine motor skills for children aged 4-5 years, 2) implementation of learning through cutting and sticking activities to improve fine motor skills in children aged 4-5 years and 3) improvement of children's fine motor skills after participating in cutting and pasting activities for children aged 4-5 years. The subjects of this study were 13 students in Group A. The form of this research is classroom action research. The data analysis used in this research is observation, interview, and documentation which is carried out in two cycles. The steps used in this study are as follows: 1). Planning, 2). Implementation, 3). Observation, 4). Reflection. Based on the results of data analysis, it was found that cutting and pasting activities could increase children's fine motor skills in the first cycle by 38.46%, increasing to 61.54% in the second cycle. These results indicate that cutting and pasting activities can improve the fine motor skills of Group A children at Aisyiyah Kindergarten Bustanul Athfal II Tumampua, Pangkep.